Hubungan Komunikasi Orang Tua dalam Keluarga dengan Prestasi Belajar Siswa di SMP N 30 Padang - Ismaniar, Ismaniar; Delmi, Putri Apri (Universitas Negeri Padang, 2024)
This research was motivated by the author's observations at State Junior High School 30 Padang. From the observations made, it appears that there are still many students who get low test scores. This research aims to obtain data and information regarding the relationship between parental communication in the family and student learning achievement at State Junior High School 30 Padang. The population in this study was 39 students and the research sample was 31 students. The sampling method applied by researchers was Stratified Proportional Random Sampling. The instrument used is a questionnaire with a Likert scale model. The data was analyzed using the rank order formula. The results show that there is a very significant relationship between parental communication in the family and student learning achievement at State Junior High School 30 Padang.